Exploring Teacher’s Pupils Experiences of Physical Education in Baku Primary Schools - Sodiya, Oluwaseyi Olubunmi (ADA University, 2020)
This study aimed at exploring teacher’s pupils’ experiences of physical education in Baku primary schools, physical education is an educational subject linked to maintaining the human body through physical exercise and developing knowledge of our body. As stated in the general education concept of the national curriculum of Azerbaijan under the purpose of education is to transfer to the children's sensitivity, aesthetic and artistic taste, moral and spiritual qualities, physical training and self-service skills. The road map to reducing insufficient physical activity level among primary school pupils is to ensure that physical education classes are being delivered as stated in the Azerbaijan national education curriculum with the availability of facilities and equipment such as a playground, pitch, open space for the free place to encourage pupils’ participation in physical education and physical activity at school. This study is an explanatory sequential research design concept data collection process through a quantitative survey and qualitative teacher’s reflection was used to understand teachers’ and pupils' experiences of school based physical education with the total numbers of one hundred and seventy-one pupils and five teachers. The findings of the study show that students are not having enough physical education lesson at schools and less physical activity participation due to lack of facilities, swapping of physical education lesson with other subjects considered important and one hundred and forty eight pupils confirmed that it affected their participation in physical education. Other factors such as time duration between thirty to forty minutes twice a week is also a piece of evidence that pupils have a low level of physical education lesson. The teacher’s reflection on the result also stated that physical education lesson should be every day with an increase in time duration. The teachers agreed that swapping of physical education lesson, lack of facilities and equipment are the main barriers confronting the student’s participation in physical education and physical activity in schools around Baku. The teachers highlighted the value and significance of pupil’s participation in physical education such as health perspective and academic improvement in the reflection. In conclusion, this study has provided indication for teachers, school leaders and stakeholders in education to identify some of the needs for school-based physical education and pupil’s participation.
Keywords: Education; Physical Education.; Physical Education -- Azerbaijan.; Education -- Azerbaijan.